2008
DOI: 10.1063/1.3026654
|View full text |Cite
|
Sign up to set email alerts
|

Relaxations in Ba2BiSbO6 double complex perovskite ceramics

Abstract: The electric properties of the complex double perovskite Ba 2 BiSbO 6 have been investigated using impedance spectroscopy in the frequency range from 1 Hz up to 1 MHz and in the temperature range from room temperature up to 560 K. There are two contributions to the electrical properties due to the grain and grain boundary. The oxygen vacancies play an important role in the conductivity and strongly increase the dielectric constant at high temperatures. The analysis of the frequency dependence of the conductivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 43 publications
(48 reference statements)
0
14
0
Order By: Relevance
“…charge carriers are the same in HCZ, which may be interpreted as polaron hopping between neighbouring sites within the crystal lattice. The activation energy for the relaxation associated with the bulk is substantially lower than that observed in some other double perovskites, such as Ba 2 AlNbO 6 (0.49 eV) [45], Ca 2 FeSbO 6 (0.60 eV) [46], Ba 2 FeSbO 6 (0.75 eV) [47] and Ba 2 BiSbO 6 (1.14 eV) [5]. This bulk activation energy has a magnitude of the order of oxygen vacancy motion [48].…”
Section: Electric Modulus Formalismmentioning
confidence: 75%
See 2 more Smart Citations
“…charge carriers are the same in HCZ, which may be interpreted as polaron hopping between neighbouring sites within the crystal lattice. The activation energy for the relaxation associated with the bulk is substantially lower than that observed in some other double perovskites, such as Ba 2 AlNbO 6 (0.49 eV) [45], Ca 2 FeSbO 6 (0.60 eV) [46], Ba 2 FeSbO 6 (0.75 eV) [47] and Ba 2 BiSbO 6 (1.14 eV) [5]. This bulk activation energy has a magnitude of the order of oxygen vacancy motion [48].…”
Section: Electric Modulus Formalismmentioning
confidence: 75%
“…The double perovskite oxides with general formula A 2 B 0 B 00 O 6 have attracted a great deal of attention due to their scientific as well as technological importance [1][2][3][4][5][6][7]. Double perovskites have shown promise in the development of spin polarized conduction and ferromagnetic semiconductors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two sets of relaxations were frequently reported in different type of materials including double peroskite, and were always ascribed to the contributions from grain and grain boundary [13][14][15][16][17][18][19][20]24]. The impedance spectrum is extremely advantageous for distinguishing grain and grain boundary contributions [25].…”
Section: Resultsmentioning
confidence: 99%
“…The results reported by Castro et al. revealed that Ba 2 BiSbO 6 show multi-relaxations [13]. Lin et al reported a relaxor-like dielectric behavior in La 2 NiMnO 6 [14] and La 2 CoMnO 6 [15].…”
Section: Introductionmentioning
confidence: 99%